Congenital solitary reticulohistiocytosis (Hashimoto - Pritzker) - Luciana Prates Nogueira de Lima; Carolina Viza Amorim; Rachel Martins Marinho; Maria Letícia Cintra; Elemir Macedo de Souza (Sociedade Brasileira de Dermatologia, 2022)
Abstract Congenital and self-healing Hashimoto-Pritzker reticulohistiocytosis is the benign variant of the Langerhans cell histiocytosis (LCH) group. It is characterized by multiple skin lesions (congenital or appearing during the first days after birth), without systemic manifestations and spontaneous resolution in days to months. The authors report the case of a boy with a single congenital leg skin lesion, a rare disease variant. Through histopathology, a dense skin infiltration of S100 protein-, CD1a-, CD207-immunomarked cells was found. KI67 index was high (62%). A complete spontaneous resolution occurred 07 days after the biopsy (25 days after birth). Monolesional disease, distal limb lesion, absence of lesions in the mucous membrane or seborrheic area, and less than 25 percent of LCs with Birbeck granules were said to be possible clues for a favorable prognosis in LCs histiocytosis. But, as a precautionary measure, the child will be followed up until at least 2 years of age.